High prevalence of congenital thrombophilia in patients with pregnancy-related or idiopathic venous thromboembolism/pulmonary embolism - Ikejiri, Makoto; Wada, Hideo; Yamada, Norikazu; Nakamura, Maki; Fujimoto, Naoki; Nakatani, Kaname; Matsuda, Akimasa; Ogihara, Yosihito; Matsumoto, Takeshi; Kamimoto, Yuki; Ikeda, Tomoaki; Katayama, Naoyuki; et al. (International journal of hematology, 2017)
Congenital thrombophilia which is characterized by deficiencies in proteins such as antithrombin (AT), protein C (PC) and protein S (PS), is a major cause of venous thromboembolism (VTE). A total of 130 patients with VTE were evaluated for congenital thrombophilia based on the activity of AT, PC, or PS. Fifteen VTE patients with congenital AT deficiency (11.5 %), 16 with congenital PC deficiency (12.3 %) and eight with congenital PS deficiency (6.2 %) were diagnosed using DNA analysis. The frequency of congenital AT deficiency was significantly higher in subjects with pregnancy-related and idiopathic VTE than in those with VTE due to other causes, and congenital PC and PS deficiency were frequently associated with idiopathic VTE. Among the groups examined, the plasma levels of AT were the lowest in subjects with pregnancy-related VTE. Although our findings may have been influenced by some unintentional bias, congenital thrombophilia is nevertheless a major cause of VTE in pregnant patients as well as in young or middle-aged patients without any underlying diseases.